2021
DOI: 10.1002/jclp.23151
|View full text |Cite
|
Sign up to set email alerts
|

Working with social withdrawal, or hikikomori, in Japan: From shame to pride

Abstract: The term hikikomori, or social withdrawal, was first coined in the late 1980s in Japan to describe adolescents and young adults who isolated themselves at home, withdrew from most social engagement, such as work or school, and had almost no relationships with others (except family members and online contacts) for longer than 6 months. Hikikomori often results from emotional injuries such as rejection, or failures that have not been addressed or even noticed. In the current case illustration, the problem of hik… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…There is a dearth of studies on the relationship between HLID and employability. In an ideographical study, Iwakabe [ 91 ] reported that some people with HLID tend to gain employment but are often prone to quit and that quitting tends to herald reclusive isolation. It is also important to reiterate that this study occurred a year after the SARS-COV-2 outbreak, when ‘working from home’ and remote work became more commonplace and, at times, even encouraged after the lifting of social restrictions.…”
Section: Discussionmentioning
confidence: 99%
“…There is a dearth of studies on the relationship between HLID and employability. In an ideographical study, Iwakabe [ 91 ] reported that some people with HLID tend to gain employment but are often prone to quit and that quitting tends to herald reclusive isolation. It is also important to reiterate that this study occurred a year after the SARS-COV-2 outbreak, when ‘working from home’ and remote work became more commonplace and, at times, even encouraged after the lifting of social restrictions.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are consistent with the results of other cross‐sectional studies (Garofalo et al, 2020; Leavitt et al, 2020), revealing that describing, acting with awareness, and nonjudging can act as negative predictors of aggression and NSSI by the shame‐proneness's mediating effects. Shame is considered as one variety of social pain (Boring et al, 2021; Elison et al, 2006, 2014; Iwakabe, 2021). As MacDonald and Leary (2005) hypothesizing that because social pain coopted the physical pain mechanisms, the links extend to physical threat‐defense mechanisms proposed by researchers (Jonas et al, 2014; Park et al, 2023), the results of current study can be explained by the threat‐defense mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Owing to the importance of psychological capital for hikikomori, this study sought to investigate the therapeutic outcomes of psychological capital among three kinds of therapy: cognitive-behavioral, narrative, and play therapies, which were implemented on hikikomori based on their unique needs and situations underlying their social withdrawal state [e.g., ( 3 , 4 , 7 )]. Cognitive-behavioral therapy helps deal with hikikomori’s maladaptive thoughts and fosters their adaptive behavioral coping capabilities ( 12 , 13 ); narrative therapy helps enhance hikikomori’s sense of self ( 14 ); play therapy helps enhance hikikomori’s social skills, sense of teamwork, cognitive capabilities, and leadership qualities that equip them with the requisite capabilities to handle issues in their daily lives ( 15 ).…”
Section: Introductionmentioning
confidence: 99%
“…Reviewed by existing literature, this group of youth experience various negative life events such as parental issues, bullying, difficulty in fitting into society, and stigma related to prolonged social withdrawal [e.g., (3)(4)(5)(6)]. Not being able to deal with these negative experiences, they develop "a strong sense of failure and inadequacy, " disempowerment, a low level of self-confidence, and a sense of hopelessness for the future [ (3,7), p. 1207; (6)]. This contributes to their engagement in social withdrawal behavior as a coping strategy (3,6).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation